Through Women’s Eyes: A Study of Vulnerability in 2015 Earthquake - Gurung, Devi (Dhaulagiri Journal of Sociology and Anthropology, 2019)
The effects of disasters as being differentiated across the spectrum of sociological categories have received wider acceptance through a number of scholarly articles. In the context of Nepal, a disaster prone country, the social science scholars came to their big awakening of the long established anecdotes only after Gorkha earthquake hit the country in 2015. This qualitative research, conducted through a case study in earthquake hit Gamchha in outskirts of Kirtipur town in Kathmandu, where fifteen female respondents were interviewed in long form, puts itself in a gap, left out by the previous scholars who largely missed the post-disaster experiences of the women corresponding to their different social categories and contexts. It takes a close-up of a nuanced and a step-wise process to flesh out gender, disaster as being sociologically biased towards women, and in due course targets the gap within the category of women through the gendered perspective of disaster. Showing the pointers to the existing gaps in the approach toward the disasters, the differentiated policies are intrinsically prescribed to address the demands of women depending upon their positionality in the social landscape.